PEMBERDAYAAN KEMANDIRIAN EKONOMI ANAK PANTI MELALUI PELATIHAN KEWIRAUSAHAAN ; STRATEGI MEMULAI DAN MENGELOLA USAHA KECIL DI PANTI ASUHAN ULIL ABSHAR SENGKALING MALANG - Murdiono, Murdiono; Yusuf, Muhammad; Roziqi, Muhammad Ainur (Jurnal Pepadu, 2025)
This community service program was carried out at Ulil Abshar Orphanage, Sengkaling, Malang, with the primary objective of empowering the economic independence of orphanage children through entrepreneurship training. The main challenges faced by the children are the lack of practical skills and limited experience in managing small businesses, which necessitates systematic capacity building. The implementation methods included several stages, namely the provision of conceptual materials on entrepreneurship, technical training on starting small businesses, and mentoring in managing simple business units aligned with local potentials and needs. Furthermore, the children were encouraged to develop creativity in producing marketable products and to practice digital technology–based marketing strategies. The results of the program demonstrated an improvement in the children’s understanding of entrepreneurship concepts, their ability to design business plans, and their skills in independently managing small businesses. This activity also fostered greater self-confidence, entrepreneurial motivation, and awareness of the importance of economic independence for their future. Thus, this entrepreneurship training is expected to serve as an initial step in preparing a generation of independent, productive, and competitive orphanage children. Program sustainability is planned through continuous monitoring, further mentoring, and the development of collaborative networks with various stakeholders.